(untitled) (Indian Journal of Animal Production and Management, 2024)
Understanding the pivotal role of wallowing in water buffaloes is imperative in designing appropriate housing systems that cater to their species-specific behaviours and innate requirements. Wallowing, a behaviour allowing buffaloes to cope with high levels of heat and humidity facilitates evaporative heat loss, serving as their primary mechanism for heat regulation. This is particularly crucial due to their limited sweat glands and heat-absorbing black skin. However, the shift from extensive to intensive husbandry practices has curtailed wallowing opportunities for buffaloes, potentially jeopardizing their well-being. This review underscores the significance of wallowing for water buffaloes and its profound effects on their thermoregulation, behaviour, productivity, reproductive responses, and health considerations. Additionally, it delves into the motivations and challenges associated with providing wallowing opportunities in intensive husbandry systems.